Surface Modification of Tools by Electrical Discharge Treatment in Electrolyte - Krastev, Dimitar; Yordanov, Boyan; Paunov, Veselin (Micro and Nanosystems, 2014)
In this work is described a novel technique for surface modification of metals and its application for obtaining higher hardness and wear resistance of tools. The electrical discharge treatment in electrolyte gives a modified surface with specific combination of properties in result of nonequilibrium microstructural characteristics. The surface layers have a different structure in comparison with the metal matrix and higher hardness, wear resistance and corrosion resistance. The modification goes by a high energy thermal process in a very small volume on the metallic surface involving melting, vaporisation, activation and alloying in electrical discharges, and after that cooling of this surface with high rate in the electrolyte. The high energy process put together with the nonequilibrium phase transformations in the metallic system causes considerable modifications of the metallic surface and obtaining layers with fine-crystalline and nano-crystalline structure. The investigations show that layers obtained on tool steels have hardness which leads to a considerable increase in working life of tools and wide opportunities for industrial application.
Keywords: tool steels